Purification and identification of rotenone from derris elliptica by using the vacuum liquid chromatography-thin layer chromatography (VLC-TLC) method - Zubairi, Saiful Irwan; Sarmidi, M. R.; Aziz, R. A.; Ramli, M. K. A.; Latip, R.; Nordin, N. I. A. (2004)
History has recorded the use of rotenone as bio-pesticide by plant and vegetables growers worldwide. The reintroduction of this bio-active compound as an environmental friendly bio-pesticide in organic fruits and vegetables plantations is now an emergent trend. Our laboratory is focused on the development of bio-pesticide using rotenone extracted from local Derris elliptica. Liquid chromatographic method with high vacuum pressure was developed for the analysis of rotenone in the crude extract of Derris elliptica. The treated root and stem were cut into small pieces prior to extraction process using the Normal Soaking Extraction (NSE) method. The crude extract was concentrated further by using rotary evaporator at 40 0C under reduced pressure of 800 mbar. A high-pressure vacuum liquid chromatographic was then carried out for the purification of rotenone using silica gel (230 mesh to 400 mesh) with variety of eluents polarity (hexane, chloroform, acetone and ultra pure water respectively). All eluents that have been collected after the purification process were subjected to the semi-automatic TLC (CAMAG Linomat 5) for the identification of rotenone and other constituents by using an isocratic elution with a mixture of petroleum ether and ethyl acetate with a ratio of 4:2. The markers for each bio-active constituent were visualized and recorded using UV lamp (wavelength of 254 nm and 365 nm) and the Rf values for desirable constituent (rotenone) was calculated respectively. The employed method shows significant improvement in rotenone separation and purification compared to the normal TLC method.